2021
DOI: 10.3390/molecules26206121
|View full text |Cite
|
Sign up to set email alerts
|

The Procyanidin C1-Dependent Inhibition of the Hydrolysis of Potato Starch and Corn Starch Induced by Pancreatin

Abstract: Procyanidins are contained in various foods, and their effects on starch hydrolysis have been reported. In Japan, black soybeans, which contain a trimeric procyanidin, procyanidin C1 (proC1), are cooked with rice and used to prepare dumplings. In this study, the effects of proC1 on the pancreatin-induced formation of reducing sugars and starch hydrolysis were studied using potato starch and corn starch. ProC1 inhibited both reactions; the inhibition was greater in potato starch than corn starch when added to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The slowdown might be due to C3G-dependent combining of two amylose molecules. Some flavonoids have been reported to be able to combine two amylose molecules 15 , 20 , 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slowdown might be due to C3G-dependent combining of two amylose molecules. Some flavonoids have been reported to be able to combine two amylose molecules 15 , 20 , 21 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that the slow starch digestion of rice cooked with adzuki bean may be due to the binding of the degradation products of procyanidin to amylose 12 , 13 . Furthermore, it has been reported on the contribution of procyanidins to slow down amylose hydrolysis of non-glutinous rice flour heated with BSB extract 14 and on the mechanism of slowdown of amylose hydrolysis in corn starch and potato starch heated with procyanidin C1 15 . Taking the reports into account, we postulated that the hydrolysis of a reagent amylose might be slowed down by heating with BSB extract.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying the incubation with pancreatin, the absorption spectrum of starch-iodine complexes in each fraction was changed decreasing the absorbance at all wavelengths examined. It has been reported that the absorbance of starch-iodine complexes decreases in a first-order like reaction in a range of incubation time ( Takahama et al., 2021a , 2021b ; Takahama and Hirota, 2021 ). Then, the absorbance decrease was plotted semi-logarithmically at 500, 550, and 700 nm, which would reflect the concentration of starch with shorter, middle, and longer glucose chains, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it has been reported that proanthocyanidins are effective to slow down starch hydrolysis by inhibiting starch digestive enzymes such as α-amylase ( Barret et al., 2013 ; Gonçalves et al. 2011 ; Lee et al., 2007 ), and by forming complexes with amylose and amylopectin ( Amoako and Awika, 2019 ; Barros et al., 2012 ; Takahama and Hirota, 2021 ; Takahama et al., 2019 ). If proanthocyanidins can slow down the hydrolysis of starch in the intestine, the rise of blood sugar can be reduced by taking food, which were prepared from cereals such as rice and wheat and proanthocyanidin-rich ingredients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation